Perspective of 3D printing in dentistry—Exploring the new horizon - Krishna Takkella, Bharani; Venkata Anusha, Nayanala; Sujanamulk, Bhavana; Naffizuddin, Mohammad; Kishore Jammalamadugu, Raj; Pinjari, Hameeda; Chaitanya Krishna, Thakkella; Balaji, Lokanathan; Manasa, Mummidi; Kosuru, Vamseedhar (Trends in Immunotherapy, 2023)
The phrase “3D printing” is frequently used to illustrate a fabrication technique that constructs objects by sequentially adding layers. Additive manufacturing, commonly referred to as rapid prototyping or “solid free-form technology”, is a name that more appropriately reflects this method. As a result of the advancement of this technology, 3D objects are converted into 3D photos that are then precisely and perfectly reproduced as required. Using this technique, normal 2D systems are used to visualise 3D objects that are typically seen in radiology. From the perspectives of numerous dental disciplines, including orthodontics, endodontics, prosthodontics, and periodontics, 3D printing technology has been expanding its application in experimental, clinical, and educational sides of medicine and dentistry. It involves innovation and research, training, treatment modalities and education while utilising the swiftly advancing 3D printing technology. It is a promising clinical tool since it makes it possible to see how treatments are working. The use of 3D-printed models in educational programmes encourages students and trainees to practise their dental skills. The improvement of dental education, clinical treatment, and research could all be made possible by the use of 3D printing.